PENGARUH TRANSPARANSI KERJA TERHADAP KUALITAS PELAYANAN KESEHATAN DI RSUD MIMIKA - MELITA, KARTIKA; LENGKONG, FLORENCE DAICY; PLANGITEN, NOVVA (Sam Ratulangi University, 2019)
Transparency is openness regarding information relating to organizations that areeasily available and can be accessed by stakeholders. Transparency has succeeded in creating ahorizontal accountability between local governments that are clean, effective, efficient,accountable and responsive to the aspirations and interests of the community. Transparencywhich is meant in this research is the openness of access for the community in obtaining healthservices in the Mimika Regional Hospital. The problem to be answered in this study is about worktransparency which influences the quality of health services in the Mimika Regional Hospital.This study uses Quantitative Research Methods. Has two variables, namely Variable (X) WorkTransparency and Variables (Y) Quality of Health Services. Transparency variables are measuredfrom several dimensions, namely informative (informative) dimensions and disclosure dimensions(disclosure). Health Service Quality Variables have 5 (five) dimensions namely reliability,assurance, tangible, empathy, and responsiveness. Both of these variables are measured throughadjusted dimensions and indicators. The results showed that work transparency had a positive andsignificant effect on the quality of health services in the Mimika Regional Hospital. Thus it canbe said that with good transparency it can improve the quality of health services, especially in theMimika Regional Hospital. Based on the results of the study, it is expected that the MimikaRegional Hospital will stick to the principle of work transparency so that it can improve the qualityof health services in the Mimika Regional Hospital.Key Words : Influence, Transparency, Work, Quality of Health Services